Residual transmission of schistosomiasis in Ndikinimeki Health District (Centre Region, Cameroon) despite implementation of complementary control strategies: Prospects for elimination - Hervé Kengne Fogang; Hugues C. Nana Djeunga; Alvine C. Kengne-Fokam; Murielle C. Tchami Mbagnia; Flobert Njiokou; Dickson S. Nsagha; Emmanuel Yenshu; Joseph Kamgno (Parasite Epidemiology and Control)
Schistosomiasis control currently relies on school-based preventive chemotherapy (PC) with praziquantel, which has been proven, unfortunately, insufficient to interrupt disease transmission in areas with persistent transmission. In the Ndikinimeki Health District (Centre Region, Cameroon), complementary strategies (community-based preventive chemotherapy, water sanitation, hygiene, and health education) have also been implemented to accelerate the interruption of schistosomiasis transmission in this focus. The assessment of the impact of this package of interventions revealed that only a few individuals were still infected with Schistosoma mansoni. This study, therefore, aimed to investigate whether schistosomiasis transmission has been interrupted in the Ndikinimeki Health District by assessing the infection among the population of snails, intermediate hosts of schistosomiasis. A cross-sectional malacological survey was conducted in four health areas of the Ndikinimeki Health District using a standardized technique. Collected snails were transported to the laboratory, where they were identified and exposed to sunlight for cercarial shedding. Overall, 350 snails intermediate hosts of schistosomes were collected in 32 sampling sites. A total of 330 (94.3 %) were identified as Biomphalaria pfeifferi and Biomphalaria camerunensis, and 20 (5.7 %) as Bulinus forskalii. Of the 154 snails that survived during 30 days of follow-up, 16 (10.4 %; 95 % CI: 6.5–16.2) shed cercariae, the infection rate being quite heterogeneous between snails' species and communities. This study revealed a residual transmission of schistosomiasis in the snail populations, emphasizing the need for snail control to complement current interventions and accelerate schistosomiasis transmission interruption.